BUSINESS STRATEGY FOR THE DEVELOPMENT OF MSMES IN NORTH PADANG LAWAS - Hardana, Ali (INTERNATIONAL, Journal of Sharia Business Management, 2026)
This study aims to examine the business strategy for the development of Micro, Small, and Medium Enterprises (MSMEs) in North Padang Lawas. In the digital era, MSMEs face both opportunities and challenges in utilizing digital platforms for marketing, sales, and business management. This research employs a quantitative approach using surveys as the primary data collection method. Respondents include MSME actors who actively use digital tools, such as social media and e-commerce platforms, in their business operations. Data were analyzed using descriptive statistics and multiple regression analysis to determine the impact of digital business strategies on MSME performance. The results indicate that social media marketing, e-commerce adoption, and digital promotion strategies significantly improve sales, expand market reach, and enhance competitiveness. However, challenges such as limited digital literacy, resource constraints, and uneven internet access hinder full implementation. The study suggests that proper planning of digital business strategies, combined with support from government and relevant institutions in the form of training and infrastructure, is crucial to optimize MSME growth and sustainability in North Padang Lawas.